Improving Learning Time Management Using Problem Solving Techniques in Group Guidance Activities - Indah Nur Raniah; Siti Muyana (International Journal of Pedagogy, 2023)
The background of this research is based on the phenomenon that occurs that success in learning is influenced by flexible and regular study time management. The purpose of this study was to determine the effectiveness of group guidance problem solving techniques to improve student learning time management. The research used quantitative methods, namely experiments. Research subjects class VIII E students at SMP Negeri 2 Moyudan who have been selected according to the sufficient category. Data collection techniques used scale and observation. Data analysis techniques used the T-test formula. The results showed that based on the results of paired samples t-test, pretest and posttest were obtained. sig.(2-tailed) value of 0.000 then compared to the sig. 5% = 0.05, it can be determined that 0.000 < 0.05 means that Ho is rejected and Ha is accepted. The conclusion is that group guidance services using problem solving techniques is effective to improve student learning time management at SMP Negeri 2 Moyudan.